Random‐Cavity Lasing from Electrospun Polymer Fiber Networks. (30th October 2014) - Krämmer, Sarah; Vannahme, Christoph; Smith, Cameron L. C.; Grossmann, Tobias; Jenne, Michael; Schierle, Stefan; Jørgensen, Lars; Chronakis, Ioannis S.; Kristensen, Anders; Kalt, Heinz
<x xml:space="preserve">Abstract</x> Lasing emission from random cavities formed in networks of electrospun Rhodamine‐doped polymer fibers is presented. Spatially resolved spectroscopy and spectral analysis prove that the observed laser emission stems from individual ring resonators randomly distributed throughout the network. These electrospun fiber lasers represent a facile and straightforward configuration for developing novel photonic devices that may advantageously utilize the network morphology. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>